Rancang Bangun Sistem Persediaan Alat Tulis Kantor Berbasis Web Pada Perumdam Tirta Kerta Raharja Kabupaten Tangerang - Nur Azizah; Nurlaila Suci Rahayu; Dewi Anjani (UNIVERSITAS RAHARJA, 2021)
An office stationery inventory system that is accurate and up to date is needed by the company. In the process of stationery inventory of the Tirta Kerta Raharja District Office in Tangerang Regency, which is done at this time is still manual so it is less effective, because the warehouse sub-section utilizes office stationery inventory documents in the form of submission forms and inputs office stationery inventory data manually so that the monitoring process is difficult and vulnerable to loss or damage to documents. Therefore, it is necessary to design a computerized web-based office stationery inventory information system in order to facilitate its users. With the computerized web- based office stationery inventory system can facilitate the warehouse subsection in inputting data so that inventory monitoring is carried out regularly to make it more accurate and optimal. Data collection methods are done by observation, interviews, and literature studies from various studies, while the system analysis method is done using the PIECES method and the design method uses UML (Unified Modeling Language) and PHP programming language and MysQL as a database. This is the rationale for how researchers analyze the existing office stationery inventory system at the Tirta Kerta Raharja Public Corporation in the District of Tangeran so that it can facilitate the performance to be more effective, efficient and accurate.